2003
DOI: 10.1080/1042819021000054661
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Medical Resource Utilisation and Costs of Hyperuricemia and Tumour Lysis Syndrome in Patients with Acute Leukaemia and Non-Hodgkin's Lymphoma in Four European Countries

Abstract: Hyperuricemia (HU) and tumour lysis syndrome (TLS) are complications of acute leukaemia and non-Hodgkin lymphoma (NHL) leading to increased morbidity and mortality. The objective of this study was to define incidence and calculate health care cost associated with HU and TLS. 788 acute leukaemia and NHL patients from Belgium, The Netherlands, Spain and UK were screened retrospectively for HU and TLS. Resource use related to HU and TLS was recorded and costs were calculated applying local unit costs. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 12 publications
1
83
0
9
Order By: Relevance
“…Razis et al 24 reported that the incidence of LTLS was 57% among 41 patients with hyperleukocytic acute leukemia (WBC >100×10 9 /L), which was comparable to the 45% found in our study (data not shown). In the study by Annemans et al, 20 the incidence of hyperuricemia in 204 patients with AML was 14%, but the incidence of LTLS was not reported. In a recently published series of 194 patients with AML or advanced myelodysplastic syndrome, 8 the incidence of LTLS was 10%, lower than the 17% found in the present study.…”
Section: 2mentioning
confidence: 99%
“…Razis et al 24 reported that the incidence of LTLS was 57% among 41 patients with hyperleukocytic acute leukemia (WBC >100×10 9 /L), which was comparable to the 45% found in our study (data not shown). In the study by Annemans et al, 20 the incidence of hyperuricemia in 204 patients with AML was 14%, but the incidence of LTLS was not reported. In a recently published series of 194 patients with AML or advanced myelodysplastic syndrome, 8 the incidence of LTLS was 10%, lower than the 17% found in the present study.…”
Section: 2mentioning
confidence: 99%
“…In relation to the underlying malignancy, the respective percentages were 2.5% in ALL patients, 2.2% in AML patients and 3.9% in NHL patients. 9) Tumor lysis syndrome is most commonly observed following chemotherapy for high-grade lymphoproliferative malignancies such as acute lymphoblastic leukemia (ALL) and Burkitt's lymphoma. Other hematologic malignancies that have been less commonly associated with it include chronic lymphocytic leukemia, 10) acute myeloid leukemia and plasma cell disorders.…”
Section: Discussionmentioning
confidence: 99%
“…TLS is often associated with haematological malignancies (Fleming and Doukas, 1992;Hande and Garrow, 1993;Lawrence, 1994;Veenstra et al, 1994;Kadar and Krumerman, 1995;Hogan and Rosenthal, 1998) but it is also observed in various solid tumours (Mahmoud et al, 1998) with high proliferative rates and high response rate to cytotoxic therapy such as testicular cancer, breast cancer, ovarian cancer, etc. Available facts suggest that the incidence of clinical TLS is approximately 3-7% for acute leukemias and 4-11% for lymphomas (Annemans et al, 2003;Wossmann et al, 2003). However certain subgroups of leukemia patients, such as those with mature B acute lymphoblastic leukemia (ALL) and Burkitt's lymphoma/ leukemia, have been reported to have a high frequency of TLS of around 25% (Stapleton et al, 1988;Montesinos et al, 2008).…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%